PRESERVICE SCIENCE TEACHERS’ ATTITUDES TOWARDS SCIENTIFIC RESEARCH (DICLE UNIVERSITY SAMPLE) - İbrahim Ümit YAPICI (International Journal of Eurasia Social Sciences, 2017)
The aim of this research is to examine the preservice biology, physics, chemistry and science teachers’ attitudes towards scientific research according to the class level, department and gender. Data were collected from 191 preservice teachers who are studying at Dicle University in 2016-2017 academic year. The research was conducted in the survey model. The "Scale of Attitude towards Scientific Research" developed by Korkmaz, Şahin and Yeşil (2011) was used as data collection tool. As a result of the research, the biology, physics, chemistry and science teachers' attitudes towards the scientific research are generally positive. It is seen that there is no significant difference according to "class", "department" and "gender".